Prototipe Automatic Air Filtration Memanfaatkan Mikrokontroler ATmega328 Sebagai Air Quality Control - Ahmad Roihan; Muhamad Asep Damyati (Politeknik Harapan Bersama, 2018)
The growing awareness of the global community in creating and maintaining healthy air quality, encouraging various institutions and companies to implement environmental management system. Through proper supervision and control, environment with clean air condition will improve the productivity of employees in the workplace and reduce the number of absentee employees with ill reasons that can hinder the production process in the company. Environmental management system implemented at PT. Inter World Steel Mills Indonesia, encouraging the company to better air control quality in the work environment. To support the ongoing environmental management system, an Arduino-based air monitoring and control device is established which can detect air pollution and control it with air filtration and inform air quality level through short message service to related parties. The aim of this research is to determine the air quality levels and then improve the air quality that will have a positive impact on the environment and health of employees.